The efficacy and neuroplasticity of Tuina combined with repetitive transcranial magnetic stimulation in the treatment of post-stroke depression: study protocol for a single-center, randomized, controlled trial - Ma, Zhao; Gao, Zhengkun; Chen, Xiao; Hu, Yuqian; Gao, Hang; Gu, Jinying; He, Haoxiang; Jin, Hui; Tao, Jiming; Fang, Min (Frontiers in Neurology, 2025)
IntroductionPost-stroke depression (PSD), characterized by low mood and low interest, is the most common complication after stroke. The limitations of PSD drug therapy often require multidisciplinary combination therapy in clinical practice. Tuina therapy and repetitive transcranial magnetic stimulation (rTMS) have shown potential in modulating neural plasticity and improving depressive symptoms. However, the combined efficacy of these non-pharmacological therapies on PSD and their underlying mechanisms remain underexplored. This study aims to investigate the clinical effectiveness of massage combined with rTMS in treating PSD and explore its impact on brain functional networks and neuroendocrine mechanisms.Methods and analysisThis study is a non-inferiority randomized controlled trial (RCT). One hundred and twenty-eight participants with PSD will be randomly assigned (1:1) to the intervention group (Tuina + rTMS treatment) and the control group (cognitive behavior treatment). The primary efficacy outcome is the change from baseline to week 2 in Hamilton Depression Rating Scale (HAMD) and Functional Magnetic Resonance Imaging (fMRI). Secondary efficacy outcomes include other assessments of the Mini-Mental State Examination (MMSE), The modified Barthel index (MBI), The National Institutes of Health Stroke Scale(NIHSS), inflammatory factor (IL-6, IL – 17, TNF-α, IFN-γ, IL-4, IL-10), and Functional near-infrared spectroscopy (fNIRS). Efficacy and scale assessments will be conducted at 1 month and 3 months after the completion of treatment.DiscussionThis trial will provide reliable evidence on the efficacy of Tuina combined with rTMS in treating PSD and explore its impact on brain functional networks and neuroendocrine mechanisms.